Meningkatkan Kemampuan Melukis dalam Pembelajaran SBDP Melalui Metode Drill and Practice Bagi Siswa Tunarungu - Wike Nadillah Delzaen; Martias Z (Jurnal Penelitian Pendidikan Khusus, 2023)
Learning improvement in improving painting skills in SBDP learning with fine art material is discussed in this study. This research is an example of a classroom action research project where the classroom teacher acts as the observer and the researcher teaches the lesson. The purpose of this research is to demonstrate how the Drill and Practice method can help deaf students paint more proficiently. The planning, action, observation, and reflection stages of this research were carried out over two cycles, each of which had four meetings. These stages were analyzed both qualitatively and quantitatively. The results of the study found that the use of the drill and practice method in SBDP learning was able to improve the painting skills of deaf students. The final result of the action given is the average value of students who previously only got 62 which is below the specified KKM value of 75. In cycle I students got an average value of 78 which still experienced obstacles and basic mistakes. So that after the second action in cycle II students get an average score of 91 which exceeds the KKM. It can be said that the drill and practice method in SBDP learning can improve the painting ability of deaf childrenÂ